PENGARUH ONLINE REVIEWS TERHADAP ONLINE HOTEL BOOKING INTENTIONS, STUDY KASUS PADA TRAVELOKA - Marie, Andhalia Liza; Widodo, Rintis Eko (Jurnal Ilmiah Pariwisata, 2019)
The growth of internet information and communication technology is increasing. This makes consumers more critical in hotel booking activities through websites / applications that affect brand image and buying interest. As the internet grows, word-of-mouth electronics has become an important phenomenon. The purpose of this study was to analyze the effect of online reviews found on the Traveloka site on the consumer's overnight stay. This study uses a quantitative approach. The sample of this research is 105 respondents who have read online reviews on the Traveloka site. This study uses multiple linear regression analysis techniques. From the results of the study note that online review has a positive effect on interest in staying.